(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
This study was carried out to find out the financial profitability and technical efficiency of tilapia fish farmers in the selected area of Bangladesh. A total of 70 tilapia fish farmers (large 36 farmers and small 34 farmers) were selected from major tilapia producing area at Trishal upazila of Mymensingh district in Bangladesh. To fulfill the objectives of this study, profitability, socioeconomic analysis, Cobb-Douglas production function and Data Envelopment Analysis (DEA) were employed. Study revealed that gross profit margin of the large farmers was 24.42% and small scale farmers was 23.8% indicating that farmers did not enough well in managing their farm and farmers has less capacity to cover for operating, financing and other cost. Break-even price for the large tilapia farmers worked out Tk. 77.33 per kg and small farmers was Tk. 81.56 per kg while break-even production for large farmers was found 1159.64 kg per hectare. Benefit cost ratio, net profit margin were found more than one and positive respectively, indicated that tilapia farming was commercially profitable. Considering all selected farmers, tilapia farming found a profitable business where undiscounted BCR for large farmers was 1.213 and a small farmer was 1.230. The mean technical efficiency level of tilapia fish farmers was 81.8 (where allocative efficiency was 93.1 and scale efficiency was 88.2) percent, implies that by operating at full technical efficiency levels, tilapia yield could be increased and efficient farmers found more productive than inefficient farmers. The results of technical efficiency showed that the farmers were efficient nevertheless, the sample farmers operated well below the production frontier and hence that they still had a chance to achieve targeted yields. Farmer’s financial benefit can be increased by reducing the feed price or increasing the output price. Int. J. Agril. Res. Innov. Tech. 12(1): 120-128, June 2022